Two Understandings of "Soft Power": Prerequisites, Correlates and Consequences - P. Parshin (Vestnik MGIMO-Universiteta)
The category of "soft power" suggested by Joseph Nye in early 1990s is analyzed in the paper as one of realization of tactile metaphor. Highlighted are those cognitive semantic peculiarities of this metaphor which contribute to its wide popularity and, at the same time, produce prerequisites for two dramatically different understandings of "soft power". According to technological understanding, "soft power" is an instrument or, broader, a technology, especially a communicative one, applied in world politics in such a way as to minimize damage caused to the object of power exertion in comparison to other, "hard power" instruments. In accordance with resource understanding, "soft power" is peculiar to influence exerted by an actor due to his/her/its attractiveness and shared values. The author analyses political and ideological correlates of these two understandings and relates them to different traditions in the study of country image and reputation, namely international relations theory and nation branding.. Analyzed are also the most topical disagreements about the "soft power" in the discourse of world politics.